Microbubble Delivery Platform for Ultrasound-Mediated Therapy in Brain Cancers - Kibeom Kim; Jungmin Lee; Myoung-Hwan Park (MDPI AG, 2023)
The blood-brain barrier (BBB) is one of the most selective endothelial barriers that protect the brain and maintains homeostasis in neural microenvironments. This barrier restricts the passage of molecules into the brain, except for gaseous or extremely small hydrophobic molecules. Thus, the BBB hinders the delivery of drugs with large molecular weights for the treatment of brain cancers. Various methods have been used to deliver drugs to the brain by circumventing the BBB; however, they have limitations such as drug diversity and low delivery efficiency. To overcome this challenge, microbubbles (MBs)-based drug delivery systems have garnered a lot of interest in recent years. MBs are widely used as contrast agents and are recently being researched as a vehicle for delivering drugs, proteins, and gene complexes. The MBs are 1-10 μm in size and consist of a gas core and an organic shell, which cause physical changes, such as bubble expansion, contraction, vibration, and collapse, in response to ultrasound. The physical changes in the MBs and the resulting energy lead to biological changes in the BBB and cause the drug to penetrate it, thus enhancing the therapeutic effect. Particularly, this review describes a state-of-the-art strategy for fabricating MB-based delivery platforms and their use with ultrasound in brain cancer therapy.